Global and regional myocardial function and outcomes after transcatheter aortic valve implantation for aortic stenosis and preserved ejection fraction. Issue 3 (March 2020) - Reskovic Luksic, Vlatka; Postolache, Adriana; Martinez, Christophe; Dulgheru, Raluca; Ilardi, Federica; Tridetti, Julien; Nguyen, Mai-Linh; Piette, Caroline; Pasalic, Marijan; Bulum, Josko; Separovic Hanzevacki, Jadranka; Lancellotti, Patrizio
Abstract : Aim: To investigate the effects of transcatheter aortic valve implantation (TAVI) on early recovery of global and segmental myocardial function in patients with severe symptomatic aortic stenosis and preserved left ventricular ejection fraction (LVEF) and to determine if parameters of deformation correlate with outcomes. Methods: The echocardiographic (strain analysis) and outcome (hospitalizations because of heart failure and mortality) data of 62 consecutive patients with preserved LVEF (64.54 ± 7.97%) who underwent CoreValve prosthesis implantation were examined. Results: Early after TAVI (5 ± 3.9 days), no significant changes in LVEF or diastolic function were found, while a significant drop of systolic pulmonary artery pressure (PAP) occurred (42.3 ± 14.9 vs. 38.1 ± 13.9 mmHg, P = 0.028). After TAVI global longitudinal strain (GLS) did not change significantly, whereas significant improvement in global mid-level left ventricular (LV) radial strain (GRS) was found (−16.71 ± 2.42 vs. −17.32 ± 3.25%; P = 0.33; 16.57 ± 6.6 vs. 19.48 ± 5.97%, P = 0.018, respectively). Early significant recovery of longitudinal strain was found in basal lateral and anteroseptal segments ( P = 0.038 and 0.048). Regional radial strain at the level of papillary muscles [ P = 0.038 mid-lateral, P < 0.001 mid-anteroseptum (RSAS)] also improved. There was a significant LV mass index reduction in the late follow-up (152.42 ± 53.21 vs. 136.24 ± 56.67 g/m 2, P = 0.04). Mean follow-up period was 3.5 ± 1.9 years. Parameters associated with worse outcomes in univariable analysis were RSAS pre-TAVI, LV end-diastolic diameter after TAVI, relative wall thickness, and mitral E and E / A after TAVI. Conclusion: Global and regional indices of myocardial function improved early after TAVI, suggesting the potential of myocardium to recover with a reduced risk for clinical deterioration.